Notes: Conditions for the Applicability of the Regenerative Method - Glynn, Peter W.; Iglehart, Donald L. (Management Science, 1993)
The regenerative method for estimating steady-state parameters is one of the basic methods in simulation output analysis. This method depends on central limit theorems for regenerative processes and weakly consistent estimates for the variance constants arising in the central limit theorems. A weak sufficient condition for both the central limit theorems and consistent estimates is given. Previous authors have implicitly made stronger moment assumptions which have led to strongly consistent variance estimates, more than is needed for the regenerative method to hold. The relationship between conditions for the validity of the regenerative method and those for the validity of standardized time series methods is also discussed.